2009
DOI: 10.1111/j.1469-1809.2008.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

R58fs Mutation in the HGD Gene in a Family with Alkaptonuria in the UAE

Abstract: SummaryThis study was conducted to determine the prevalence of alkaptonuria in the UAE population and to identify the genotype of affected individuals. In a 3 stage sampling technique 2981 pupils from Government schools in Al Ain and private schools in Dubai were selected to take part in the study, of whom 2857 provided urine samples. Urine collected was analysed for homogentisic acid by gas chromatography-mass spectrometry. Genomic DNA was isolated from the white blood cells of all family members of the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The Centre for Arab Genomic Studies (CAGS) 6,[18][19][20][21] In the case of isovaleric aciduria, three mutations (p.R392H, p.R395Q and p.F382fs) were reported in four unrelated Emirati families and one mutation (p.E408K) in an Egyptian family. 20 Alkaptonuria, due to the single nucleotide deletion of c.342delA (c.174delA), was reported in a family from Al Ain, UAE; the allelic prevalence was estimated at about 1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Centre for Arab Genomic Studies (CAGS) 6,[18][19][20][21] In the case of isovaleric aciduria, three mutations (p.R392H, p.R395Q and p.F382fs) were reported in four unrelated Emirati families and one mutation (p.E408K) in an Egyptian family. 20 Alkaptonuria, due to the single nucleotide deletion of c.342delA (c.174delA), was reported in a family from Al Ain, UAE; the allelic prevalence was estimated at about 1%.…”
Section: Discussionmentioning
confidence: 99%
“…20 Alkaptonuria, due to the single nucleotide deletion of c.342delA (c.174delA), was reported in a family from Al Ain, UAE; the allelic prevalence was estimated at about 1%. 21 In the UAE, screening began for PKU in 1995, for congenital hypothyroidism in 1998, sickle cell disease in 2002, congenital adrenal hyperplasia in 2005 and biotinidase deficiency in 2010. [22][23][24] The Expanded National Neonatal Screening Programme, implemented in 2011, covers over 90% of all neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Abdulrazzaq et al [2009] screened 2,981 school children for homogentisic acid and identified a family with high levels of this metabolite indicating alkaptonuria. Table 9 lists the mutations identified in some metabolic disorders in the UAE.…”
Section: Metabolic Disorders Including Neurodegenerative Disordersmentioning
confidence: 99%
“…Few studies have been conducted to determine the genotype of affected individuals with AKU and mutations in the HGD gene in arab population. Abdulrazzaq et al [18] found a single-nucleotide deletion c.342delA in exon 3 in a family with AKU in the United arab emirates, which resulted in a frameshift at amino acid position 58 (R58fs) [18].…”
Section: Discussionmentioning
confidence: 98%